Survey for karlotoxin production in 15 species of gymnodinioid dinoflagellates (Kareniaceae, Dinophyta)1 - Mooney, B; Miguel de Salas; Gustaaf Hallegraeff; Place, AR (2009)
Toxin analysis of 15 species of Kareniaceae revealed the presence of karlotoxin, KmTx 2, in only a single species (Karlodinium veneficum) but with variable activity in strains from the Swan (KmSwanTx 2-1, 2.1 pg Æ cell)1; and KmSwanTx 2-2, 0.53 pg Æ cell)1), Huon (KmHuonTx 2, 0.86 pg Æ cell)1), and Derwent rivers (<0.001 pg Æ cell)1) in Australia. A newly isolated Southern Ocean species, Karlodinium conicum, contained a novel poorly hemolytic karlotoxin analogue (KmconicumTx, 2.8 pg Æ cell)1). The hemolytic potency (HD50%) of the Australian karlotoxins were as follows: KmSwanTx 2-1 (65.9 ± 4.8 ng) and KmSwanTx 2-2 (63.4 ± 3.7 ng), KmHuonTx 2 (343 ± 4.9 ng), and KmconicumTx (>4,000 ng). Species from the closely related genera Takayama (T. helix, T. tasmanica, T. tuberculata), Karenia (K. asterichroma, K. brevis, K. mikimotoi, K. papilionacea, K. umbella), and Karlodinium (Ka. australe, Ka. antarcticum, Ka. ballantinum, Ka. corrugatum, Ka. decipiens) were all consistently negative for karlotoxin production. Brevetoxin (PbTx) was only detected in K. brevis, and hemolytic activity was only observed in Ka. veneficum strains.